Evaluation of antibiofilm and catalytic activity of biogenic silver nanoparticles synthesized from Acacia nilotica leaf extract. (8th November 2018) - Arya, Geeta; Mankamna Kumari, R; Sharma, Nikita; Chatterjee, Sreemoyee; Gupta, Nidhi; Kumar, Ajeet; Nimesh, Surendra
Abstract: In the current research of bacteriology, the biofilm infections are becoming serious issues. The biofilm has potential resistant towards antibiotics, even at higher concentration, due to the protective covering that enable unavailability of these antibiotics towards bacteria residing inside. Thus to combat these problems, biogenic silver nanoparticles (AgNPs) of spherical shape were synthesized having potential against biofilm forming bacteria. Here, we focused on the green synthesis owing to its inherent features such as simplicity, eco-friendliness, cheap rate and rapidity. We have synthesized AgNPs using the aqueous extract of Acacia nilotica leaf. The bioactive compounds present in the extract are responsible for the reduction of to . The synthesis conditions were optimized using critical parameters and the optimized one was then characterized via UV-Vis spectroscopy, dynamic light scattering, transmission electron microscopy, x-ray diffraction and Fourier transform infrared spectroscopy. Further, synthesized AgNPs were used to evaluate strong antibacterial activity and catalytic potential that was assessed against degradation of anthropogenic pollutant 4-NP and azo dyes: methylene blue and congo red.